Interacting behaviours that mother's exhibit during motherchild interaction between hearing-imp aired and normal-hearing children - Fletcher, Gabriel Matthew (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
The aim of this study was to compare and determine the interacting behaviours of Malay Kelantanese speaking of hearing mothers to their hearing-impaired or normal-hearing children during mother-child interaction. Each group consisted of six mother-child dyads and ten categories of interacting behaviours were analyzed. The results indicated that the interacting behaviours of the mothers of the two groups varied within groups. However, on comparison, the two groups; mothers of hearingimpaired children and mothers of normal-hearing children showed no statistically significant difference (p > 0.05). Results revealed that the mothers of hearingimpaired children portrayed more of teacher and manager behaviour style but less exhortation, helper, positive and negative verbalization, nonverbal reinforcer, and positive and negative facial expression in the context of free play. The clinical implications of these findings are associated with the culture, education, and experience of the mother.